2018
DOI: 10.1177/0276236618771537
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Their Children’s Parasocial Relationships: The Recontact Study

Abstract: Parent report measures indicate that young children's parasocial relationships (PSRs) are multidimensional constructs consisting of dimensions such as social realism, attachment and character personification, and human-like needs. However, little is known about how parent perceptions of these dimensions evolve as children mature and form new PSRs. In this 3-year follow-up study, parents (N ¼ 156) from two previous studies were recontacted, and they provided updated information about their children's PSRs in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
(270 reference statements)
1
8
0
Order By: Relevance
“…Poke´mon GO players report about their favorite Poke´mon character from the past yielded two factors: attachment and friendship and human-like needs, which are consistent with prior reports about children's PSRs with media characters (Aguiar, Richards, Bond, Brunick, & Calvert, 2018;Richards & Calvert, 2016. Different motivations for Poke´mon GO app play occurred in this study, with nostalgic as the reason for younger adults' play and to improve physical activity for older adults' play.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Poke´mon GO players report about their favorite Poke´mon character from the past yielded two factors: attachment and friendship and human-like needs, which are consistent with prior reports about children's PSRs with media characters (Aguiar, Richards, Bond, Brunick, & Calvert, 2018;Richards & Calvert, 2016. Different motivations for Poke´mon GO app play occurred in this study, with nostalgic as the reason for younger adults' play and to improve physical activity for older adults' play.…”
Section: Resultssupporting
confidence: 86%
“…PSRs are multidimensional constructs (Bond & Calvert, 2014). Both parent and child measures of PSRs include the dimensions of attachment and friendship, social realism, and human-like needs (Aguiar, Richards, Bond, Brunick, & Calvert, 2018;Richards & Calvert, 2016. Attachment and friendship is an individual's emotional connection to a favorite media character, which includes trusting one's favorite media character and treating that character like a friend (Richards & Calvert, 2016.…”
Section: Pokémon Go and Motivation For Physical Activitymentioning
confidence: 99%
“…Although research on the relationship qualities children attribute to virtual characters remains sparse, considerable efforts have been made to examine young children's parasocial relationships with wellestablished media characters (e.g., Aguiar, Richards, Bond, Brunick, & Calvert, 2019;Bond & Calvert, 2014a;. In a survey study conducted with parents of preschoolers, Bond and Calvert (2014a) found that children's relationships with their favorite media characters were made up of three dimensions: (a) "attachment" in which the character makes the child feel comfortable and safe;…”
Section: Parasocial Relationshipsmentioning
confidence: 99%
“…According to parent reports of their preschool-aged children, PSRs with media characters are multidimensional constructs, consisting of feelings of attachment and character personification (e.g., perceiving the character as a safe and trusted friend), social realism (e.g., perceiving the character as lifelike), and humanlike needs (i.e., viewing the character as having physical and psychological needs; Richards & Calvert, 2016). By about ages 5 to 8, parent reports also revealed that character qualities (perceiving the character as attractive, intelligent, nice, and strong) emerged as a new dimension of PSRs (Aguiar, Richards, Bond, Brunick, & Calvert, 2018).…”
Section: Young Children’s Psrs: Definition and Measurementmentioning
confidence: 99%
“…Our findings, however, might underestimate the frequency with which parasocial breakups occur in older children. A parent report study indicated that as many as 77% of children forged new PSRs with different media characters over the course of a 3-year period (Aguiar et al., 2018). The increase in PSRs with new media characters over time suggests that many former favorite media characters might be dropped entirely, gradually fade away, or remain a friend to children—just not their favorite friend.…”
Section: Frequency Of Prs Breakupsmentioning
confidence: 99%